2009
DOI: 10.4049/jimmunol.0903058
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood CCR4+CCR6+ and CXCR3+CCR6+ CD4+ T Cells Are Highly Permissive to HIV-1 Infection

Abstract: There is limited knowledge on the identity of primary CD4+ T cell subsets selectively targeted by HIV-1 in vivo. In this study, we established a link between HIV permissiveness, phenotype/homing potential, and lineage commitment in primary CD4+ T cells. CCR4+CCR6+, CCR4+CCR6−, CXCR3+CCR6+, and CXCR3+CCR6− T cells expressed cytokines and transcription factors specific for Th17, Th2, Th1Th17, and Th1 lineages, respectively. CCR4+CCR6+ and CXCR3+CCR6+ T cells expressed the HIV coreceptors CCR5 and CXCR4 and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
412
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(452 citation statements)
references
References 71 publications
35
412
0
Order By: Relevance
“…This discrepancy is probably due to differences in the cell types analyzed. We determined viral infection by using the entire population of CCR5-transfected CD4 + primary T or Jurkat CD4 + cells (40% transfection efficiency), whose expression of CCR5 resembled that of activated primary T cells and Th1 cells (54,55), whereas our analysis of the mechanism involving actin polymerization was restricted to CCR5 + cells. Our data concur with a report that, in NIH 3T3 cells coexpressing CD4, CXCR4, and CCR5, the T-tropic HIV-1 isolate HCF was less infective than in CCR5-negative cells (56); another study showed lower infectivity of primary X4 viruses (ELI 1 and K4) in HeLa-CD4 cells when CCR5 was coexpressed (57).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy is probably due to differences in the cell types analyzed. We determined viral infection by using the entire population of CCR5-transfected CD4 + primary T or Jurkat CD4 + cells (40% transfection efficiency), whose expression of CCR5 resembled that of activated primary T cells and Th1 cells (54,55), whereas our analysis of the mechanism involving actin polymerization was restricted to CCR5 + cells. Our data concur with a report that, in NIH 3T3 cells coexpressing CD4, CXCR4, and CCR5, the T-tropic HIV-1 isolate HCF was less infective than in CCR5-negative cells (56); another study showed lower infectivity of primary X4 viruses (ELI 1 and K4) in HeLa-CD4 cells when CCR5 was coexpressed (57).…”
Section: Discussionmentioning
confidence: 99%
“…The X4 HIV strain infected mainly T H 1T H 17, T H 17 and, to a lesser degree, T H 2 cells. Because a similar surface expression of CXCR4 was observed on all four cell types, this suggests that there are additional post-entry mechanisms that permit viral replication [35]. Similarly, CCR5 expression on T cell subsets correlated poorly with levels of integration of the R5 HIV strain.…”
Section: Involvement Of Ccr6 In Cellular Hiv Pathogenesis T H 17 Cellsmentioning
confidence: 75%
“…In HIV-infected individuals, CCR6 + T cells harboured more viral DNA than CCR6 À T cells [35]. The X4 HIV strain infected mainly T H 1T H 17, T H 17 and, to a lesser degree, T H 2 cells.…”
Section: Involvement Of Ccr6 In Cellular Hiv Pathogenesis T H 17 Cellsmentioning
confidence: 95%
See 2 more Smart Citations